ANALISIS MEKANISME PENENTUAN PLAFON KREDIT PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA (PPPK) PADA PUD BPR BANK KARANGANYAR - Bekti Indah Fatmawati (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
The purpose of this study is to analyze the mechanism for determining the credit limit for government employees with work contracts (PPPK) at the Regional Public Company of the People's Economic Bank Karanganyar, focusing on aspects of creditworthiness analysis and risk management. The method applied is a qualitative approach with a case study. Data collection techniques consisted of interviews, observations, and documentation to gain a comprehensive understanding of the credit ceiling determination process. Data analysis was performed descriptively and qualitatively to understand the procedures and policies applied. The results showed that PUD BPR Bank Karanganyar applies the principle of prudence in creditworthiness analysis and effectively manages credit risk in accordance with the applicable regulations, namely the "Guidelines for Credit Policies and Procedures for People's Economic Banks".